Faktor-Faktor Yang Berhubungan Dengan Loyalitas Karyawan di Rumah Sakit Harapan Bunda Kota Batam - Resi Novia; Yulastri Arif; Mutia Amalia Lubis (Jurnal Keperawatan Muhammadiyah, 2020)
The loyalty of an employee is required in the sustainability of the hospital, but the problem of loyalty is still a concern because many impacts can be generated at the hospital. This study aims to identify factors related to employee loyalty in Harapan Bunda Hospital Batam in 2015. The study design was analytic descriptive, cross-sectional approach. Samples 186 employees with proportional random sampling. Statistical test results obtained personal characteristic factors which are related to employee loyalty is the need of employees with p = 0.001 and attitude of employees with p = 0.001. There is no correlation between job characteristics and loyalty of employees. The needs of the employees is the most dominant factor related to employee loyalty with OR = 17.938. Coaching and human resource management needs to be improved so that employees have a high concern for the hospital, feeling of belonging, to prevent turnover, improving performance for the sustainability of the hospital, still have the motivation to work, can improve the professionalism and productivity of labor thus improving the quality of hospital services can be achieved.